French-German and Polish-German Textbook Dialogues as Elements of the Reconciliation Processes after World War II - Kąkolewski, Igor (Sensus Historiae, 2026)
International textbook dialogues and transnational history textbook projects play significant roles in the pursuit of reconciliation processes in Europe and the world at the beginning of the 21st century. Notable examples are the Franco-German Histoire/Geschichte and the German-Polish Europa - Unsere Geschichte / Europa. Nasza historia, two binational history textbook series. Both educational publications might be seen as a result of the long-lasting transnational textbook dialogue between historians in France, Germany and Poland, and also as key waypoints in the broader European reconciliation efforts after World War II.